Narrative of bilingual children: general productivity and lexical diversity - Blažienė, Agnė (Taikomoji kalbotyra, 2015)
The paper deals with the narrative production of developing Lithuanian bilingual children (L1 – Lithuanian, L2 – English). The material was collected in four Lithuanian language schools based in London. The study employs the method of story generation. During the experiment, the participants were asked to tell a story according to a 6 picture sequence Cat Story (Hickmann 2003; Gagarina et al. 2012). There were 100 Lithuanian bilingual children (4-10 years old) from middle-class families involved in the experiment. They all lived in London and attended private Lithuanian schools ( 3-6 hours per week). The narratives were recorded, transcribed and morphologically annotated for an automatic analysis of narrative language using CHILDES software. During the analysis, the general productivity and lexical diversity (the number of words, the number of utterances, mean length of utterance, type/token ratio) of the narratives were investigated. The results obtained demonstrate significant differences in productivity and lexical diversity among six age groups. The narratives of older children have been found to be longer; they also include more words, consist of more utterances, which on average are longer. A comparison of bilingual and monolingual children’s narratives has revealed that bilingual children are capable of producing more words, while the lexical diversity of nouns, verbs and adjectives is similar in bilingual and monolingual children’s narratives or, in some cases, higher in the narratives of monolingual children. These indicators of productivity and lexical diversity suggest that the native Lithuanian language acquired in a bilingual environment is similar to the Lithuanian language acquired in a monolingual language environment.